Pertumbuhan Awal Mahkota Dewa (Phaleriamacrocarpa) pada Beberapa Dosis Vermikomposdan Intensitas Naungan - MERAKATI HANDAJANINGSIH; ENTANG I. SUKARJO; NORMA LIDIAWATI (Agrotrop : Journal on Agriculture Science, 2013)
Early Growth of Phaleria macrocarpaunder Different Shade Intensity and Doses ofVermicompost. Phaleria macrocarpaisshade plant,nativeto Papua-Indonesia. This is one of themost valuable herbal plants in Indonesia and widely grown in home gardens as well as in industrialareas.Organic matter incorporated into the media can increase nutrient availability, medium moisture,plant growth regulator, and improve soil structure to support root growth. In addition, light intensity isanother factor determined the optimum growth especially on shade plants. The research was aimed tofind the most appropriate dose and shade intensity to support early growth stage of Phaleriamacrocarpa.CompletelyRandomized Design was applied in Split Plot arrangement with threereplications. The shade intensity consisted of 0, 25, 50, or 75% while the dose of vermicompostconsisted of 0, 300, 600, or 900 g polybag-1. Research showed thatno interaction was revealed betweenshade intensity and dose of vermicompost on plant height, plant fresh weight and degree of leaf greeness.Root length and root dry weight responded linierly under 25, 50, and 75% shadesThere was no responseon plant growth with the increase ofdose of vermicompost when plants were grown without shading.The highest growth as shown on leaf number, leaf area, stem diameter, and root growth was under 50%shading and application 900 g polybag-1 of vermicompost. This research thus supports the previousreport that P. macrocarpa is less tolerance to full sunlight during its early growth.